The reality of privatization in Algeria - Sociological study - Hocine TAIBI; Faiza TOUNSI (Social Sciences Journal, 1970)
The topic of Privatisation or the transfer of public property to the private sector or whatit's termed as privatisation is recently considered as a centre of noticeable internationalconcern. Most countries nowadays, with their different economic and politicalorientations went to abandon a lot of public economic institutions and giving it to theprivate sector. Before moving to the analysis of the legal and organizational frame forthe start of the privatisation of public institutions process in Algeria, we take a look atthe essence of privatisation and its real motives and reality in Algeria, then the fields ofapplying it in Algeria.